PENERAPAN PANCA USAHATANI PADI SAWAH (Oryza sativa L.) DI KAMPUNG DESAY DISTRIK PRAFI KABUPATEN MANOKWAR - Bhagaswara, Aloysius Yobelio; Yuminarti, Umi; Agus Irianto Sumule (Sosio Agri Papua, 2024)
Food is the most important basic human need. Without food, human life will end by itself. Sufficient quality food for all people is a challenge that is not easy. The approach taken to increase food production is intensification. The agricultural intensification program in Indonesia is five farming efforts which include (1) the use of superior seeds; (2) land processing; (3) fertilization; (4) pest and disease control; and (5) irrigation. Desay Village is one of the villages in Prafi District which is a rice production center that has implemented five farming businesses. The aim of this research is to analyze the level of implementation of five farming businesses in Desay Village, Prafi District. This research is descriptive research with a case study method, as the case in this research is the implementation of five lowland rice farming businesses in Kampung Desay. Respondents were taken in this research using a random sampling method. The implementation of five farming activities in Kampung Desay is already in the high category, but land processing, fertilization and pest control activities are still in the medium category. This is because farmers carry out land processing, fertilization and pest control that are not in accordance with the guidelines for lowland rice cultivation. Recommendations that can be given to improve this condition are to increase subsidies for land processing equipment (tractors) for each farmer group so that land processing can be carried out on time, then provide fertilizer subsidies to farmers so that fertilization can be done in the right dose and on time, as well as the need for counseling on farmers to carry out integrated pest control.